2017
DOI: 10.3390/w9060393
|View full text |Cite
|
Sign up to set email alerts
|

Water Use and Yield of Soybean under Various Irrigation Regimes and Severe Water Stress. Application of AquaCrop and SIMDualKc Models

Abstract: Data relative to two soybean seasons, several irrigation scheduling treatments, including moderate and severe deficit irrigation, and rain-fed cropping were used to parameterize and assess the performance of models AquaCrop and SIMDualKc, the latter combined with the Stewart's yield model. SIMDualKc applies the FAO56 dual crop coefficient approach for computing and partitioning evapotranspiration (ET) into actual crop transpiration (T c act ) and soil evaporation (E s ), while AquaCrop uses an approach that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 53 publications
3
28
0
1
Order By: Relevance
“…The employment of dripper discharge lower than 0.6 L h −1 has been recently demonstrated as an efficient method for potato growth in an arid region [14]. Due to low discharge and precise water application, drip irrigation reduces groundwater contamination, water and fertilizer waste, and energy inputs [15][16][17]. Surface or subsurface drip irrigation enables high water and oxygen availability in the root zone due to partial wetting [18].…”
Section: Introductionmentioning
confidence: 99%
“…The employment of dripper discharge lower than 0.6 L h −1 has been recently demonstrated as an efficient method for potato growth in an arid region [14]. Due to low discharge and precise water application, drip irrigation reduces groundwater contamination, water and fertilizer waste, and energy inputs [15][16][17]. Surface or subsurface drip irrigation enables high water and oxygen availability in the root zone due to partial wetting [18].…”
Section: Introductionmentioning
confidence: 99%
“…The goodness of fit statistics indicated that the model was calibrated and validated satisfactorily for selected parameters (canopy cover, soil water content, actual evapotranspiration, above ground biomass, above ground edible biomass, and water productivity) under well-watered and severe water stress conditions. The model estimated water loss to be more by evaporation than transpiration, which has been alluded by other studies (Bello and Walker, 2017;Giménez et al, 2017;Greaves and Wang, 2017;Katerji et al, 2013). This may be caused by the practice of harvesting leafy vegetables repeatedly; with the soil left bare for extended periods.…”
Section: Conclusion and Recommendationsmentioning
confidence: 82%
“…This contrast can be ascribed to the practice of harvesting biomass repeatedly; we suspect that the model assumed that the soil was left bare for a longer period during each harvesting period, resulting in higher Es losses than Tr. A study conducted by Giménez et al (2017) on soybean tested AquaCrop under five water stress levels [(full irrigation, rainfed, and deficit irrigation at; (1) flowering to grain filling, (2) vegetative period, and (3) during vegetative to grain filling)] and found that AquaCrop gave smaller Tr values and larger Es values. This is consistent with other studies (Bello and Walker, 2017;Greaves and Wang, 2017;and Katerji et al, 2013), which reported similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of IA over FAO-56 is that it can be adapted to any type of climate, while several studies pointed out underestimations in the ET c calculated by the FAO-56 approach in Mediterranean climates [39,60]. This is caused by the consideration of a single value of canopy conductance over the growing season and for the use of crop coefficients that have been determined under sub-humid conditions [6], although, in many cases, these crop coefficients have been adapted to local conditions [7,8,14].…”
Section: Model Evaluation: Advantages Main Sources Of Error and Limimentioning
confidence: 99%